Landwash Readers: A Space of Collective Reading in the Medical Humanities - Lewkowich, David (Journal of the Canadian Association for Curriculum Studies, 2009)
As readers, the sedimentations of our surrounding world ensure that we never read alone. There is an uneasy otherness in all readings, through which naming our obstacles is a bringing to the fore a consciousness of lack and flatness; what Maxine Greene calls an achievement of freedom in education as a transcendence of the given, an overcoming that is never complete. Obstacles in learning, which signify the dialectical nature of every human situation, are stirrings that engage dialogue in the place of an assumed silence, imagining the possible pluralities of subjectivity through learning on the verges of a fractured space. Within the context of this pedagogical confrontation, I examine the articulations of a reading group in the medical humanities from St. John’s, Newfoundland. Surpassing the closed nature of individual readings, such groups choose to act out their freedoms, and in doing so, interact with other people and textual forms as obstacles, where reading is a looping, a struggle, and a risking of free choice in a landspace that is forever shifting. As a commitment of an inherently social nature, Greene’s struggle for freedom in learning enables an embracing of alterity in a reader’s process of becoming; to become different from what one is, and what one is supposed to be—pursuing a curriculum of incessant rupturing, where openings and cleavages are always available. In this paper, I look at one use-value of social reading shared by members of this reading group: Resistance, and a Legitimation of Artistry in Medicine.